Exploration of antecedents behind Islamic corporate governance: evidence from Pakistan - Muhammad, Awais; Saboor, Qurat ul Ain; Khan, Ribbat; Mohd Thas Thaker, Mohamed Asmy (Allied Business Academies, 2022)
Objective: Corporate governance contains a set of associations among an organization’s management, its board of directors, its stockholders and other stakeholders as well, on the basis of which an organization is organized and focussed. Though, no one knows exactly behind the antecedents of Islamic corporate governance and also no standardized measures for the proficiency of organizations which may bring about the sustainability. The aim of the currentstudy was to explore the antecedents of Islamic corporate governance in Pakistan.